Comparison of ADO-II percutaneous occlusion and traditional surgery in the treatment of doubly committed subarterial ventricular septal defects in children - Tan, Bei; Li, Mi; Zhang, Kaijun; Zhou, Xue; Ao, Qiuyue; Yin, Dan; Cheng, Zhenli; Xiang, Ping (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThe aim of this study is to evaluate the efficacy and safety of ADO-II percutaneous occlusion and traditional open-chest surgery for treating doubly committed subarterial ventricular septal defect (dcVSD) in children.MethodsThe clinical data of 151 children with dcVSD treated at Chongqing Medical University Affiliated Children's Hospital between July 2019 and May 2024 were retrospectively analyzed. Patients were divided into a transcatheter group (percutaneous occlusion) and a surgical group (open-chest repair) on the basis of the treatment method used. Key evaluation metrics included procedural success rates, complication rates, and perioperative management parameters.ResultsOcclusion technical success was 94.9% (37/39) in the interventional sample of 39 patients. The 112 surgical patients had a 100% technical success rate. Three interventional patients had sinus rhythm before discharge, and 2 of 18 surgical patients had residual right bundle branch block at the last follow-up. The mild aortic valve prolapse of 115 individuals (76.2%) improved to varied degrees postoperatively. Of 96 individuals with preoperative aortic regurgitation, 83 exhibited no change, 49 improved, 17 developed new regurgitation, and two worsened. The two groups differed significantly in postoperative hospital stay, time to independent ambulation, operative time, mechanical ventilation, blooding amount, Blood transfusion volume, Fever within 72 h after operation, pulmonary infections, intravenous nutrition, antibiotic use, and hospitalization cost (all p < 0.05). There no serious problems were recorded the transcatheter group, including device dislodgement, cardiac or vascular perforation, death, or hemolysis. In the surgical group, one patient had residual shunting reoperation and another had infective endocarditis.ConclusionChildren with dcVSD can recover faster and safer using ADO-II percutaneous occlusion, which is minimally invasive and inexpensive. It can be the first-line treatment for selected patients.